Nectar sugar composition and pollinators for the naturalized exotic Leonurus japonicus (Lamiaceae) in central Argentina - Galetto, Leonardo (2010)
Volumes of nectar and sugar concentration were measured in different populations of the naturalized exotic Leonurus japonicus Houtt. (Lamiacaea) in central Argentina. Qualitative and quantitative nectar sugar composition were determined and compared between populations. In general, nectar sugar concentration was high and volume per flower was very low for all populations. Nectar sugars were glucose, fructose and sucrose for all populations, but sucrose clearly predominates over hexoses. Honeybees and bumblebees were recorded as the main pollinators in this region. Bumblebees preferences for sucrose-high nectars can be indicating that this exotic species can attract these pollinators and assure seed production to expand their populations. On the other hand, honeybees can use this nectar resource because they are generalist and have enzymes to break the sucrose in hexoses. New interesting studies can be settled considering the invasion process as theoretical framework, and developing field experiments to link plant reproductive biology, nectar traits and pollinator preferences.